[Cd(H2O)6]@Cd6Cl4(nico)12[Hg(Tab)2(μ-Cl)]2: a heterometallic host–guest icosidodecahedron cage via hierarchical assembly. Issue 43 (24th August 2017) - Tang, Xiao-Yan; Yu, Hong; Gao, Bin-Bin; Lang, Jian-Ping
Abstract : A reaction of [Hg(Tab)2 (nico)](PF6 ) (Tab = 4-(trimethylammonio)benzenethiolate, nico = nicotinate) with equimolar CdCl2 ·2.5H2 O afforded a unique heterometallic cage complex [Cd(H2 O)6 ]@Cd6 Cl4 (nico)12 [Hg(Tab)2 (μ-Cl)]2 . Abstract : Complexation of a preformed complex [Hg(Tab)2 ](PF6 )2 (1 ) with nicotinic acid in the presence of Et3 N afforded a mononuclear complex [Hg(Tab)2 (nico)]2 (PF6 )2 (2 ) (nico = nicotinate, Tab = 4-(trimethylammonio)benzenethiolate) which, upon subsequent treatment with one or three equiv. of CdCl2 ·2.5H2 O, gave rise to an unprecedented heterometallic cage complex [Cd(H2 O)6 ]@Cd6 Cl4 (nico)12 [Hg(Tab)2 (μ-Cl)]2 (3 ) or a simple salt of [Hg(Tab)2 ][CdCl4 ] (4 ).